(3GdeGdjI GdYGeI (B: s (3eWHhYI ebOeI dWdHI GdeGdjI h GdeMGSHI (B/ s - (3dYQGH, SGQIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3fTCI h JWhQ GdeGdjI GdYGeI h YdGbJgG HGdYdhe GdGNQi , GdfabGJ GdYGeI , GdGjQGOGJ GdYGeI , GdejRGfjI GdYGeI (B.s
(3eQGLY U(B.125s
Keywords: (3GdeGdjI GdYGeIs; (3GdfabGJ GdYGeIs